AUDIT SISTEM INFORMASI AKADEMIK MENGGUNAKAN FRAMEWORK COBIT 4.1 (STUDI KASUS IBI DARMAJAYA) - Neni Purwati (IIB Darmajaya, 2014)
Academic Information System Management that is not managed properly will result in low quality of service, low levels of customer satisfaction / student, so it can affect the level of stakeholder confidence in the institutions. The foregoing can be addressed by monitoring / evaluation periodically the implementation SIAKAD. With the monitoring of the implementation process SIAKAD expected to improve any shortcomings and weaknesses of the current system become better and in accordance with business objectives institutions. Methods used are the stages of auditing information systems, namely : Planning, Fieldwork, Reporting, Follow-up. Tool use is Framework COBIT (Control Objectives for Information and Related Technology) issued by ISACA (Information Systems Audit and Control Association). Based on the result of the calculation on any IT processes contained in the domain of Planning and Organization (PO) and Delivery and Support (DS) normally located at level 3 (defined process), so that the whole IT can achieve the level of desired doneness (expected maturity level) in level 4 (manage) then all procedures required in each process should be met. To achieve level 4 (manage) then each IT process must have a written standard procedures and communicated to all parties involved in the academic information system, that is to the managers and users of the system. Such procedures should be documented and updated periodically. From the results of the gap between the maturity level of IT governance is now at a level of maturity to be achieved, it is known in the domain PO and DS priority repairs done at the PO7 (managing IT human resources).Keywords: Audit, Information Systems, COBIT 4.1